Helicobacter pylori Antibody Reactivities and Colorectal Cancer Risk in a Case-control Study in Spain - Fernández de Larrea-Baz, Nerea; Michel, Angelika; Romero, Beatriz; Pérez-Gómez, Beatriz; Moreno, Victor; Martín, Vicente; Dierssen-Sotos, Trinidad; Jiménez-Moleón, José J.; Castilla, Jesús; Tardón, Adonina; Ruiz, Irune; Peiró, Rosana; et al. (Frontiers in Microbiology, 2017)
Background: Several studies have suggested that Helicobacter pylori (H. pylori) infection is a risk factor for colorectal cancer (CRC), while others have not confirmed this hypothesis. This work aimed to assess the relation of colorectal cancer with H. pylori seropositivity and with seropositivity to 16 H. pylori proteins, in the MultiCase-Control study, MCC-Spain. Methods: MCC-Spain is a multicase-control study carried out in Spain from 2008 to 2013. In total, 2140 histologically-confirmed incident colorectal cancer cases and 4098 population-based controls were recruited. Controls were frequency-matched by sex, age and province. Epidemiological data were collected through a questionnaire fulfilled by face-to-face interviews and a self-administered food-frequency questionnaire. Seroreactivities against 16 H. pylori proteins were determined in 1488 cases and 2495 controls using H. pylori multiplex serology. H. pylori seropositivity was defined as positivity to ≥4 proteins. Multivariable logistic regression mixed models were used to estimate odds ratios (OR) and 95% confidence intervals (CI). Results: H. pylori seropositivity was not associated with increased colorectal cancer risk (OR=0.91; 95% CI: 0.71-1.16). Among H. pylori seropositive subjects, seropositivity to Cagδ showed a lower colorectal cancer risk, and risk decreased with increasing number of proteins seropositive. Seropositivity to the most recognized virulence factors, CagA and VacA, was not associated with a higher CRC risk. No statistically significant heterogeneity was identified among tumor sites, although inverse relations were stronger for left colon cancer. An interaction with age and sex was found: H. pylori seropositivity was associated with a lower CRC risk in men younger than 65 and with a higher risk in older women. Conclusions: Our results suggest that neither H. pylori seropositivity, nor seropositivity to the virulence factor CagA are associated with a higher colorectal cancer risk. A possible effect modification by age and sex was identified.